1997
DOI: 10.1074/jbc.272.29.17961
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Volatile Anesthetic Chloroform to Albumin Demonstrated Using Tryptophan Fluorescence Quenching

Abstract: The site(s) of action of the volatile general anesthetics remain(s) controversial, but evidence in favor of specific protein targets is accumulating. The techniques to measure directly volatile anesthetic binding to proteins are still under development. Further experience with the intrinsic protein fluorescence quenching approach to monitor anesthetic-protein complexation is reported using chloroform. Chloroform quenches the steady-state tryptophan fluorescence of bovine serum albumin (BSA) in a concentration-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 43 publications
4
115
1
1
Order By: Relevance
“…Recent studies provide support for interactions of both halothane and chloroform with tryptophans of HSA and bovine serum albumin (13,14). Considerations of the bonding interactions involved and the frequencies of NNO-IR bands make tryptophan an attractive binding site for both NNO and NO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies provide support for interactions of both halothane and chloroform with tryptophans of HSA and bovine serum albumin (13,14). Considerations of the bonding interactions involved and the frequencies of NNO-IR bands make tryptophan an attractive binding site for both NNO and NO.…”
Section: Discussionmentioning
confidence: 99%
“…Specific, saturable binding of halothane and other anesthetics to bovine serum albumin and anesthetic-induced alterations in the structure or carrier function of this protein have been shown (11)(12)(13)(14)(15)(16). The anesthetic nitrous oxide (NNO) was detected at sites within human serum albumin (HSA) (5).…”
mentioning
confidence: 99%
“…The fluorescence decays of BSA were fitted with two exponentials, T1 = 6.50 ns and T2 = 2.46 ns and is consistent with the studies that lifetimes of tryptophan fluorescence are often multi exponential [28]. The longer and shorter lifetimes indicated that BSA contained two tryptophan residues that fluoresced in two different environments [29] and one of the tryptophan residues in the protein may be buried inside the hydrophobic interior of protein whereas the other tryptophan residue may be close to quencher [30]. This is in good agreement with the reports that BSA has two tryptophan residues, Trp-134 in the first domain located on the surface of molecule and Trp-212 in the second domain located within a hydrophobic binding pocket [14].…”
Section: Resultsmentioning
confidence: 95%
“…Fluorescence and synchronous fluorescence spectroscopic studies of bovine serum albumin: In addition to the proximity of bound cefepime hydrochloride to Trp residue, fluorescence quenching might result from structural change of BSA upon cefepime hydrochloride binding [42]. As is well known, the maximum fluorescence emission wavelength (λ em ) of Trp residues is closely related to the polarity of the microenvironment around Trp residues.…”
Section: Effect Of Cefepime Hydrochloride On the Conformation Of Bovimentioning
confidence: 99%